THE EFFECTIVENESS OF THE ROLL TOOTH-BRUSHING TECHNIQUE TOWARD GINGIVAL HEALTH STATUS OF TOTALLY BLIND PEOPLE - Jessica Laurent Citradi; Isnur Hatta; Aulia Azizah (FKG Unlam, 2022)
Background: Gingivitis is an inflammatory reaction that occurs in gingival tissue. Based on 2018 RISKESDAS data, gingivitis case that occurs in Indonesia reaches 13,9%. The prevalence of gingivitis in South Kalimantan is higher than Indonesia’s, that is 14,2%. The bad habit of mantaining oral health causes plaque accumulation on the marginal gingiva, which resulting in gingivitis. The said condition also affects disabled people, one of which is blind people. Tooth brushing intervention can be done in various kind. One of the recommended methods is the roll technique that effectively cleans plaque and can mantain gum health. Purpose: To analyze the effectiveness of the roll tooth-brushing technique toward the gingival health status (gingival index) of totally blind people. Methods: This research used quasi-experimental research method with non-equivalent control group design. The sampling technique was using purposive sampling with total samples were 15 people. This research was conducted in 21 days with 9 times encounter. The time span of each encounter is once in every 2 days. Gingival index examination used gingival index. The data analysis in this research was using Mann Whitney Test. Result: The Mann Whitney test result shows that p-value is 0,018, which is smaller than the alpha value that is 0,05 (p<0,05) which means that there is a difference between the case group that was given with socialization and roll brushing technique and the control group that was not given the said socialization and treatment. Conclusion: The roll tooth-brushing technique is effective for gingival health status (gingival index) of totally blind people.